Empirical Verification to Stocking’s Equations in Specifying Ability Levels Matching Maximum Information for Estimating Item Parameters in Item Response Theory - Ababneh, Imad (Jordan Journal of Educational Sciences, 2006)
The aim of the study was to provide empirical verifications to stocking’s equations for estimating item parameters in IRT. For the purpose of this study, a mental ability test, which was developed in a previous study, was used. Software’s Bilog- Mg and Excel were used to analyze the data. The findings were as follows: 1. Stocking’s equations were satisfied in specifying ability levels matching maximum information for estimating item parameters for the three logistic models. 2. Stocking’s equations were a suitable approach in specifying ability levels for estimating item parameters. However, the optimal ability levels specified by Stocking’s equations were mentioned in the text. 3. The accuracy of estimating the discrimination parameter and guessing parameter were inconsistent with the accuracy of estimating ability parameter, whereas, estimating difficulty parameter was consistent with the accuracy of estimating ability parameter. 4. Ability levels specified by Stocking’s equations contribute more than ability levels specified by equations introduced by Hambleton and Swaminthan in term of increasing accuracy of estimating guessing parameter for 3PL, and discrimination parameter for 2PL ,whereas , accuracy in estimating difficulty parameter wasn't changed